Zinc in Gut-Brain Interaction in Autism and Neurological Disorders. (23rd March 2015) - Vela, Guillermo; Stark, Peter; Socha, Michael; Sauer, Ann Katrin; Hagmeyer, Simone; Grabrucker, Andreas M.
Abstract : A growing amount of research indicates that abnormalities in the gastrointestinal (GI) system during development might be a common factor in multiple neurological disorders and might be responsible for some of the shared comorbidities seen among these diseases. For example, many patients with Autism Spectrum Disorder (ASD) have symptoms associated with GI disorders. Maternal zinc status may be an important factor given the multifaceted effect of zinc on gut development and morphology in the offspring. Zinc status influences and is influenced by multiple factors and an interdependence of prenatal and early life stress, immune system abnormalities, impaired GI functions, and zinc deficiency can be hypothesized. In line with this, systemic inflammatory events and prenatal stress have been reported to increase the risk for ASD. Thus, here, we will review the current literature on the role of zinc in gut formation, a possible link between gut and brain development in ASD and other neurological disorders with shared comorbidities, and tie in possible effects on the immune system. Based on these data, we present a novel model outlining how alterations in the maternal zinc status might pathologically impact the offspring leading to impairments in brain functions later in life.